THE EFFECTIVENESS OF THE THINK PAIR SQUARE (TPSq) COOPERATIVE LEARNING MODEL ASSISTED BY STICK MEDIA ON STUDENT LEARNING OUTCOMES IN CHEMICAL COMPOUND NOMENCLATURE - Siburian, Putri Dela; Silalahi, Yoisi Fortuna; Watulingas, Maasje Catherine; Rahmadani, Agung (FKIP USK, 2025)
Low student learning outcomes are often caused by limited student participation and the use of teacher-centered learning approaches. This study aims to determine the effectiveness of the Think Pair Square (TPSq) cooperative learning model assisted by stick media in improving student learning outcomes, particularly in the topic of chemical compound nomenclature. The research used a pre-experimental one-group pretest-posttest design with participants from class X-10 students at a senior high school (N=32). Learning outcomes were measured using tests given before and after the implementation of the model. Data were analyzed using a non-parametric Wilcoxon test. The results indicated a significant improvement in student learning outcomes, with an N-Gain score of 0.71 (high category) and an effect size of 3.85 (very strong category). The TPSq model, supported by stick media, encouraged students to think, discuss, and share ideas actively, leading to a deeper understanding of the material. In conclusion, the stick media-assisted TPSq learning model is effective in enhancing student learning outcomes in chemical compound nomenclature.